(untitled) (Revista Española de Fisiología, 1993)
The possible contribution of nitric oxide (NO) to the endothelium-dependent relaxation of isolated cat cerebral arteries was studied by examining the effects of the L-arginine (L-ARG) analogues L-canavanine and NG-nitro-L-arginine (L-NOARG) on acetylcholine-induced relaxation. L-canavanine (100 microM) as well as L-NOARG (10 microM) decreased significantly the relaxant response of acetylcholine, their effect being significantly reversed by L-arginine (10 microM) but not by D-arginine (10 microM). In resting conditions, L-NOARG (10 microM) elicited a contraction of 314 +/- 42 mg in arteries endowed with endothelium that was significantly diminished by endothelium removal to 88 +/- 35 mg, and by (10 microM) L-arginine to 135 +/- 54 mg. L-canavanine (100 microM) induced contractions in arteries with and without endothelial cells which were not statistically different. The results suggest that the endothelium of cat cerebral arteries has the ability to synthesize nitric oxide from L-arginine and to release it, even in the absence of a stimulus such as that of acetylcholine. L-NOARG seems to be a specific and powerful inhibitor of nitric oxide synthesis.